Competitive oxidation and ubiquitylation on the evolutionarily conserved cysteine confer tissue-specific stabilization of Insig-2 - Zhou, Zhang-Sen (Nat Commun, 2020)
Insig-2 is an ER membrane protein negatively controlling lipid biosynthesis. Here, we find that Insig-2 is increased in the tissues, including liver, but unaltered in the muscle of gp78-deficient mice. In hepatocytes and undifferentiated C2C12 myoblasts, Insig-2 is ubiquitylated on Cys215 by gp78 and degraded. However, the C215 residue is oxidized by elevated reactive oxygen species (ROS) during C2C12 myoblasts differentiating into myotubes, preventing Insig-2 from ubiquitylation and degradation. The stabilized Insig-2 downregulates lipogenesis through inhibiting the SREBP pathway, helping to channel the carbon flux to ATP generation and protecting myotubes from lipid over-accumulation. Evolutionary analysis shows that the YECK (in which C represents Cys215 in human Insig-2) tetrapeptide sequence in Insig-2 is highly conserved in amniotes but not in aquatic amphibians and fishes, suggesting it may have been shaped by differential selection. Together, this study suggests that competitive oxidation-ubiquitylation on Cys215 of Insig-2 senses ROS and prevents muscle cells from lipid accumulation.